2009
DOI: 10.5194/acp-9-3613-2009
|View full text |Cite
|
Sign up to set email alerts
|

Gas/particle partitioning of water-soluble organic aerosol in Atlanta

Abstract: Abstract. Gas and particle-phase organic carbon compounds soluble in water (e.g., WSOC) were measured simultaneously in Atlanta throughout the summer of 2007 to investigate gas/particle partitioning of ambient secondary organic aerosol (SOA). Previous studies have established that, in the absence of biomass burning, particulate WSOC (WSOC p ) is mainly from secondary organic aerosol (SOA) production. Comparisons between WSOC p , organic carbon (OC) and elemental carbon (EC) indicate that WSOC p was a nearly co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
120
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(145 citation statements)
references
References 80 publications
21
120
4
Order By: Relevance
“…A similarly elevated OM/OC ratio for total OM has been reported for the Southeast US (Simon et al, 2010). While it is possible that this result might be influenced by the assumptions made in the latter study, this finding is also consistent with a large role for aqSOA in this high-RH, photochemically-active location (Hennigan et al, 2009) (Fig. 2a-c).…”
Section: Correlation Of Wsoc With Rhsupporting
confidence: 77%
See 1 more Smart Citation
“…A similarly elevated OM/OC ratio for total OM has been reported for the Southeast US (Simon et al, 2010). While it is possible that this result might be influenced by the assumptions made in the latter study, this finding is also consistent with a large role for aqSOA in this high-RH, photochemically-active location (Hennigan et al, 2009) (Fig. 2a-c).…”
Section: Correlation Of Wsoc With Rhsupporting
confidence: 77%
“…Based on the measured WSOC gas/particle partitioning in Atlanta, an effective Henry's law constant K H * ∼10 9 M atm −1 for total WSOC was derived (Hennigan et al, 2009). While not pertaining to a specific compound, this value exceeds all values that are known for the physical solubility of common atmospheric organic compounds and is even higher than any derived from studies that suggest reversible oligomerization (Sect.…”
Section: Correlation Of Wsoc With Rhmentioning
confidence: 83%
“…Hennigan et al (2008) found that the fraction of WSOC in the particle phase increases sharply with RH. The positive correlation with liquid water rather than with organic matter (Hennigan et al, 2009) suggests that aqueous reactions were the dominant SOA formation process rather than gas-phase reactions. Moreover, the inorganic analysis, integrated over a 3-5 min period (limited to few data point per profiles), show an increase by a factor of 1.5 of the sulfate concentration (from 1.6 µg m −3 before the cloud formation up to 2.5 µg m −3 after the cloud formation), while the nitrate concentration do not show any significant evolution.…”
Section: Airborne In Situ Observations Of Aerosol Enhancement Near Cumentioning
confidence: 92%
“…This trend is in agreement with laboratory evidence that suggests slightly higher uptake at RH > 80% (Figs. 3 and 7 in Volkamer et al, 2009), and field measurements of water-soluble organics in particles that have shown enhanced partitioning above RH ∼75% (Hennigan et al, 2009). The major fraction of predicted SOA is comprised of products that are formed through the photochemical pathway k photochem (Sect.…”
Section: Soa Formation With Constant Glyoxal Concentrationmentioning
confidence: 99%